2023
DOI: 10.1002/ccd.30550
|View full text |Cite
|
Sign up to set email alerts
|

Improved left atrial appendage closure procedural efficiency using radiofrequency transseptal wire system

Abstract: Objective The radiofrequency (RF) needle has been shown to improve transseptal puncture efficiency and safety compared to mechanical needles. This study aimed to investigate the use of VersaCross RF transseptal wire system (Baylis Medical) to improve procedural efficiency of left atrial appendage closure (LAAC) compared to the standard RF needle‐based workflow. Methods Eighty‐one LAAC procedures using WATCHMAN FLX were retrospectively analyzed comparing the standard RF needle‐based workflow to a RF wire‐based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…The use of the VLA system is consistent with a previous study showing easier crossing of septum, without resistance or excessive tenting, using a seamless sheath‐dilator device to facilitate large delivery sheath, such as the WATCHMAN delivery sheath 12 . Previously, Whitler et al have shown that the RF‐wire based workflow can streamline LAAC procedures, improving procedure efficiency and safety by reducing fluoroscopy, device exchanges, and delivery sheath manipulation 15 . Similarly, in our study the additional benefit of the RF‐wire based approach was the optimized and direct access to the LAA, likely accounting for the overall procedural efficiency.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The use of the VLA system is consistent with a previous study showing easier crossing of septum, without resistance or excessive tenting, using a seamless sheath‐dilator device to facilitate large delivery sheath, such as the WATCHMAN delivery sheath 12 . Previously, Whitler et al have shown that the RF‐wire based workflow can streamline LAAC procedures, improving procedure efficiency and safety by reducing fluoroscopy, device exchanges, and delivery sheath manipulation 15 . Similarly, in our study the additional benefit of the RF‐wire based approach was the optimized and direct access to the LAA, likely accounting for the overall procedural efficiency.…”
Section: Discussionsupporting
confidence: 78%
“…shown that the RF-wire based workflow can streamline LAAC procedures, improving procedure efficiency and safety by reducing fluoroscopy, device exchanges, and delivery sheath manipulation. 15 Similarly, in our study the additional benefit of the RF-wire based approach was the optimized and direct access to the LAA, likely accounting for the overall procedural efficiency. operators in this study have significant experience with WATCH-MAN FLX LAAC; therefore, it is not known whether the results of this study would translate to less experienced operators.…”
Section: Discussionsupporting
confidence: 58%